Activity Testing Of Dahlia (Dahlia Variabilis) Tubers Against Escherichia Coli And Salmonella Typhi Bacteria In Vitro - Zola Efa Harnis; Nina Irmayanti Harahap; Rika Puspita Sari; Putri Andini (Institute Of Computer Science (IOCS), 2022)
Dahlia tubers are a source of carbohydrates in the form of inulin. Dried dahlia tubers are thought to contain inulin as much as 65-76% of the total carbohydrates contained. Inulin or fructoolgosaccharide is a food component that can act as a prebiotic and also as a soluble dietary fiber in humans. Inulin is thought to be able to maintain the balance of the other normal flora of the large intestine. The balance of microflora in the intestine is very necessary because these microbes can inhibit the growth of pathogenic bacteria. Escherichia coli and Salmonella typhi are among the choliform bacteria belonging to the Enterobacteriaceae family. Enterobacteriaceae are enteric bacteria or bacteria that live and can survive in the digestive tract. This study aims to compare the activity of dahlia tuber starch against Escherichia coli and Salmonella typhi bacteria by determining the activity of dahlia tuber starch. The results showed that dahlia tuber starch had antibacterial activity against Escherichia coli and Salmonella typh. Effective concentration in inhibiting Escherichia coli and Salmonella typhi bacteria at a concentration of 80% with an average LDH of 22.71 mm for Escherichia coli bacteria, while for Salmonella typhi the average LDH of 15.08 mm.